ANALISIS YURIDIS TINDAK PIDANA DALAM TINDAKAN MEDIK TERHADAP PASIEN - Sirait, Santi; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Health is a human right and one usur welfare was in accordance with the ideals of the nation of Indonesia as referred to in the Pancasila and the Preamble to the Constitution of the Republic of Indonesia Year 1945 health law is based on two principles of law principle. The first is the legal principle of the right to health care, which is care given by health workers on the basis of ability and skill applying science and medical technology. The second is, independent human rights or in other words the right to self-determination. The purpose of this thesis, namely: to determine the position of service standards in the doctor's duties and functions of law and to determine the elements of criminal acts between patients and physicians in the medical action. Type of research is a normative law. In this case I chose the study of the synchronization of the law, and which is the object of this study is the act of providing medical and legal analysis . From the results of research and analysis the authors concluded that: First Position duties and functions of service standards doctor in law, is as a guide and reference in providing medical action, prior to providing health care and medical measures physicians must understand the standard operating procedures. Standard operating procedures are a barometer of whether or not the alleged malpractice committed by doctors. When doctors make mistakes/ violations, doctors as professionals must be responsible . Legal responsibility will be given to the doctor can be ethical, civil, criminal, or administrative basis, depending on the level of error / violation committed by a doctor. Both acts were done intentionally physician / culpa and has met the elements of criminal acts , physicians should be held responsible. First, a doctor is the subject of law and already adept at taking legal action. Secondly, the inner relationship between the perpetrator and his actions, dolus / deliberate or culpa / omissions. Doctor in their profession, physicians are well aware of what was done to the patient so that the inner attitude of a doctor associated with services provided to the patient. Third, there is no reason eraser errors or forgiving. Therefore, if a doctor made a mistake and intentionally or negligent actions have met the elements of the criminal then the doctor will be penalized in accordance with applicable law. Keywords : Juridical Analysis - Crime - Medical Action - Against Patient